The Corporation as a Protagonist in Global History, c. 1550-1750 - Pettigrew, William A.; Veevers, David (Global Economic History Series, 2018)
In The Corporation as a Protagonist in Global History, William A. Pettigrew and David Veevers reinterpret the role of Europe's overseas corporations in early modern global history, uncovering their unique global sociology in the years 1550 to 1750. Readership: Academics and students interested in the history of trading corporations, European overseas enterprises, early modern global history, empire, trade and commerce, and business and economic historians.